Simultaneous Determination of Phytonadione and its Degradants by HPLC in Injectable Emulsion Formulation Used to Treat VKDB in Newborns - Mohabbat Ullah; Md. Sohel Rana; Md. Shahnowaj Bhuiyan (Current Research in Pharmaceutical Sciences, 2023)
Phytonadione, also known as Phytomenadione or Vitamin K1 is used as an Injectable emulsion is used to Newborns for the precautionary treatment for Vitamin K Deficiency Bleeding (VKDB) during birth. In the current study, A Gradient, Sensitive & Cost effective HPLC method has been developed to determine and quantify the degradants of Phytonadione and Benzyl Alcohol into Phytonadione Injectable Emulsion. The chromatographic separation was performed by GL Sciences Inert sustain HP™ C18 (250 × 4.6 mm, 3.0 μ) column. The degradants were well separated by a gradient program started with the mixture of 25 mM Ammonium Acetate in water as buffer, pH 3.5 and Methanol in the ratio of 40: 60 V/V at the flow rate of 1.0 mL min‑1 and UV detection was performed at 254 nm. The degradation products from Phytonadione and Benzyl Alcohol were well resolved from the main peaks and its other impurities by the developed method. The method was validated by complying specificity/selectivity, linearity, limit of detection (LOD), limit of quantification (LOQ), accuracy and precision following ICH Q2 (R1). The developed method in this study could be applied for the analysis of routine quality control related substances of Phytonadione Injectable Emulsion, since there is no official monograph.